(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Painting of works of art is also a very important stage, in which, starting from the perfection of the drawing, the careful preparation of the materials, the beautiful rendering of the color gamut, the perception of the main colors, and the correct assessment of the power of color in the description of various elements. Studying the creative path of Academician A. Akparov will help a lot in this regard. Academician A. Akparov’s school of creativity speaks of his high artistic education and strength.